2019
DOI: 10.1101/784298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of interictal epileptiform discharges on EEG-based functional connectivity networks

Abstract: Objective: Functional connectivity networks (FCNs) based on interictal electroencephalography (EEG) can identify pathological brain networks associated with epilepsy. FCNs are altered by interictal epileptiform discharges (IEDs), but it is unknown whether this is due to the morphology of the IED or the underlying pathological activity. Therefore, we characterized the impact of IEDs on the FCN through simulations and EEG analysis. Methods:We introduced simulated IEDs to sleep EEG recordings of eight healthy con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A study on hypsarrhythmia using source analysis revealed an association with delta activity in the occipital cortex, parietal cortex, putamen, caudate nucleus, and brainstem 130 . Patients with infantile spasms exhibited a broad increase in connectivity strength during IEDs 129 . Those studies support the involvement of ascending brainstem pathways that project widely to basal ganglia and cerebral cortex in the generation of hypsarrhythmia.…”
Section: Eeg‐fmri Studies In Epilepsymentioning
confidence: 84%
See 1 more Smart Citation
“…A study on hypsarrhythmia using source analysis revealed an association with delta activity in the occipital cortex, parietal cortex, putamen, caudate nucleus, and brainstem 130 . Patients with infantile spasms exhibited a broad increase in connectivity strength during IEDs 129 . Those studies support the involvement of ascending brainstem pathways that project widely to basal ganglia and cerebral cortex in the generation of hypsarrhythmia.…”
Section: Eeg‐fmri Studies In Epilepsymentioning
confidence: 84%
“…There have been several EEG‐fMRI studies on epileptic encephalopathy (e.g., West syndrome, Lennox–Gastaut syndrome [LGS]), that observed the regions involved in these syndromes. A study on the BOLD signals in hypsarrhythmia showed that multifocal spikes are associated with cerebral cortex (especially occipital areas) activation, whereas slow waves are associated with responses in the brainstem, thalamus, and putamen 128,129 . A study on hypsarrhythmia using source analysis revealed an association with delta activity in the occipital cortex, parietal cortex, putamen, caudate nucleus, and brainstem 130 .…”
Section: Eeg‐fmri Studies In Epilepsymentioning
confidence: 99%
“…Although interictal spikes may be randomly present in any chosen epoch, their influence on functional connectivity is limited if they are present in only a minority of time windows. This influence is limited because our approach captures stationary aspects of the reconstructed network rather than the transient spikes (40,56). However, we acknowledge that in circumstances where the majority of the recording contains spikes their influence on functional connectivity may be stronger.…”
Section: Discussionmentioning
confidence: 99%